When diamniotic twins suddenly become monoamniotic twins: spontaneous septostomy of the dividing membrane - Vidal, Angela (BMJ Case Rep, 2021)
In twin pregnancies, amnionicity and chorionicity are crucial as they strongly determine prenatal and perinatal management. First trimester ultrasound allows a highly reliable diagnosis of amnionicity and chorionicity, making it an internationally accepted standard in antenatal care. However, in rare cases, amnionicity can change from diamniotic to monoamniotic throughout pregnancy, substantially impacting perinatal management. We report the case of a confirmed monochorionic diamniotic twin pregnancy with a diagnosis of spontaneous septostomy of the dividing membrane (SSDM) at 28 weeks of gestation, resulting in a pseudomonoamniotic pregnancy. Even though SSDM is a rare condition and its sonographic diagnosis might be challenging, it should be considered if, in a known diamniotic pregnancy, there is a sudden failure to visualise the intertwin membrane truly separating both twins.